Is lack of social support associated with a delay in seeking medical care? A cross-sectional study of Minnesota and Tennessee residents using data from the Behavioral Risk Factor Surveillance System. Issue 7 (16th July 2018) - Reisinger, Matthew W; Moss, Marc; Clark, Brendan J
Abstract : Objective: Previous studies have demonstrated an association between social support and lower morbidity and mortality. Delay in seeking medical care is associated with poor health outcomes. The relationship between social support and delay in seeking medical care has not been established. We sought to determine whether lack of social support is associated with higher rates of delays in seeking needed medical care. Methods: This is a cross-sectional observational study using data from the 2013 and 2014 Centers for Disease Control Behavioral Risk Factor Surveillance System. Participants who were asked questions about delays in medical care and social support were included. The primary outcome was a self-reported delay in seeking needed medical care. The primary independent variable of interest was a dichotomised measure of social support. Multivariable logistic regression was performed, adjusting for demographics, socioeconomic status, comorbidities and access to care. Results: Participants without social support were more likely to report delaying needed medical care when compared with participants with social support (38%vs19%, p<0.001). The association between lack of social support and delays in care persisted after adjustment for demographics, socioeconomic status, comorbidities and access to care (OR 1.72; 95% CI 1.45 to 2.06; p<0.001). Conclusions: Lack of perceived social support is associated with patient-reported delay of needed medical care. This association may contribute to the poor health outcomes experienced by those with a lack of social support.